The chromosome‐level genome of female ginseng (Angelica sinensis) provides insights into molecular mechanisms and evolution of coumarin biosynthesis. (4th November 2022) - Han, Xiaoxu; Li, Cheng; Sun, Shichao; Ji, Jiaojiao; Nie, Bao; Maker, Garth; Ren, Yonglin; Wang, Li
SUMMARY: Coumarins are natural products with important medicinal values, and include simple coumarins, furanocoumarins and pyranocoumarins. Female ginseng ( Angelica sinensis ) is a renowned herb with abundant coumarins, originated in China and known for the treatment of female ailments for thousands of years. The molecular basis of simple coumarin biosynthesis in A. sinensis and the evolutionary history of the genes involved in furanocoumarin biosynthesis are largely unknown. Here, we generated the first chromosome‐scale genome of A. sinensis . It has a genome size of 2.37 Gb, which was generated by combining PacBio and Hi‐C sequencing technologies. The genome was predicted to contain 43 202 protein‐coding genes dispersed mainly on 11 pseudochromosomes. We not only provided evidence for whole‐genome duplication (WGD) specifically occurring in the Apioideae subfamily, but also demonstrated the vital role of tandem duplication for phenylpropanoid biosynthesis in A. sinensis . Combined analyses of transcriptomic and metabolomic data revealed key genes and candidate transcription factors regulating simple coumarin biosynthesis. Furthermore, phylogenomic synteny network analyses suggested prenyltransferase genes involved in furanocoumarin biosynthesis evolved independently in the Moraceae, Fabaceae, Rutaceae and Apiaceae after ζ and ε WGD. Our work sheds light on coumarin biosynthesis, and provides a benchmark for accelerating genetic research and molecular breeding in A. sinensis . Significance Statement: The genomic resources of Angelica sinensis in this study will facilitate efficient germplasm exploration, facilitate comparative and functional genomics studies, and the improvement of A. sinensis for medicinal uses, especially for the specific production of bioactive molecules in planta .